The effects of parenteral prostacyclin therapy as add-on treatment to oral compounds in Eisenmenger syndrome. Issue 5 (21st November 2019) - D'Alto, Michele; Constantine, Andrew; Balint, Olga Hajnalka; Romeo, Emanuele; Argiento, Paola; Ablonczy, Laszlo; Skoro-Sajer, Nika; Giannakoulas, George; Dimopoulos, Konstantinos
Pulmonary arterial hypertension (PAH) develops in 5–10% of patients with congenital heart disease (CHD) [1], and PAH associated with congenital heart disease (PAH-CHD) accounts for a significant proportion of PAH cases (34–42%) [2]. Eisenmenger syndrome is at the extreme end of the spectrum of PAH-CHD, with an untreated 10-year mortality rate of 30–40% [3]. Despite decreasing incidence in developed countries [4], Eisenmenger syndrome is likely to remain a common complication of CHD in low- to middle-income countries [5]. In this European cohort of Eisenmenger patients, prostanoid therapy, as part of triple combination therapy, was found to be safe and effective in improving exercise capacity, natriuretic peptide levels and haemodynamic parameters over a 2-year period http://bit.ly/2Zl3W1Z